Utilizando o cinema como ferramenta didática no ensino de ciências naturais - Encarnação, Rosiele Oliveira da (2020)
The teaching of Natural Sciences (Biology, Chemistry and Physics) is surrounded by a universe of formulas, concepts, structures, reactions, elements, equations that, when entering the school environment, often generate difficulties for students to understand these contents. In this sense, cinema, which is a media artifact, emerges as an alternative to address scientific themes in a contextualized, dialogical and reflective way. In this way, Cinema can bring another look to the area of Natural Sciences, with another way of acting in the classroom, in order to make the school environment a motivating space for learning. Thus, this research aimed to analyze the use of Cinema associated with The Scaffolded Reading Experience in the Teaching of Natural Sciences as a didactic tool in Elementary and Secondary Education. For this, it carried out pedagogical interventions in two different spaces: in a Federal Institute of the South of Brazil, in the Integrated High School, having as target audience students with low performance in the disciplines of the area; and in a Municipal Elementary School, located in the municipality of Jari. For the development of the work, it relied on action research and the construction and implementation of the action was guided by The Scaffolded Reading Experience, which is organized in two phases: planning and implementation. In planning, the construction of the pedagogical proposal took place, which was developed in the next phase. The implementation phase takes place in three stages, which are: pre-reading, where an Initial Questionnaire (IQ) was applied; the reading, that corresponded to the accompanying script and the showing of the film or series episode; and post-reading in which discussions were held about the contents worked on in the film/series, elaboration of activities by students and a Final Questionnaire (QF). The research results are described in three scientific articles, two implementations undertaken in high school with 1st year students in Physics and 3rd year in Chemistry and one in Elementary School with 6th year students in Science.The data obtained in this research indicate that Cinema allowed the approach to scientific content in a playful way, allowing students with difficulties in understanding, a different language to work with scientific themes, attracting their attention and improving school performance. Throughout the implementation stages, growth was perceived, expressed in the differences from the Initial Questionnaire to the Final Questionnaire, with the elaboration of complex responses articulating with the scientific aspects found in the films. Therefore, from this research it is possible to perceive the potential of Cinema and The Scaffolded Reading Experience as alternatives in the teaching-learning process in the teaching of Natural Sciences, bringing to the school environment possibilities to make the classes playful, articulate environments, motivating, dialogical, capable of assisting in the construction of students' scientific knowledge.